Effect of neuraminidase on the expression of the 3-fucosyl-N-acetyllactosamine antigen in human tissues. - Howie, A J (1985)
The monoclonal antibody AGF4.48 detects the 3-fucosyl-N-acetyllactosamine carbohydrate structure and reacts with a variety of human tissues, as shown by an immunoperoxidase method on paraffin sections of formalin fixed material. The intensity and distribution of the immunoperoxidase reactivity were affected by treatment of sections with neuraminidase. In some sites, such as bone marrow, brain, breast, and pituitary, the reaction was more intense after neuraminidase treatment. In several organs, including kidney, oesophagus, pancreas, submandibular gland, and uterus, the reaction was more widespread after neuraminidase treatment. Other organs, such as liver, lung, lymph node, skin, and uterine tube, showed an altered distribution of reactivity with AGF4.48 after sections were treated with neuraminidase. These results show that the 3-fucosyl-N-acetyllactosamine antigen is cryptic in many tissues. The antigen is masked to a variable extent in different tissues by neuraminic acid residues and can be revealed by the simple procedure of pretreating sections with neuraminidase. The value of using AGF4.48 antibody in combination with the enzyme neuraminidase to show accessible and cryptic antigen is that this reveals distinctive patterns of sialylation within various normal tissues. Whether similar patterns occur in disease will be of particular interest.